2018
DOI: 10.1177/1687814017747145
|View full text |Cite
|
Sign up to set email alerts
|

A prediction model of the surface topography due to the unbalance of the spindle system in ultra-precision fly-cutting machining

Abstract: In ultra-precision fly-cutting machining, the aerostatic spindle is the key component, which has significant influence on the machined surface quality. The unbalanced spindle directly affects the machining accuracy. In this article, a prediction model of machining surface topography is proposed which involves the effect of the gas film performance of spindle in microscale. With the Weierstrass function, unstable transient response of the aerostatic spindle system is derived by the motion model of the spindle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…They found that the imbalance in the spindle causes unbalanced magnetic forces in the motor, which ultimately affects the surface finish accuracy. In the analyses by Huang et al, 19 Chen et al, 20 and Zhang et al, 21 it was assumed that the bearing dynamic stiffness coefficient and damping coefficient were constant. However, the dynamic stiffness and damping of air bearings change with bearing clearance and rotational speeds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the imbalance in the spindle causes unbalanced magnetic forces in the motor, which ultimately affects the surface finish accuracy. In the analyses by Huang et al, 19 Chen et al, 20 and Zhang et al, 21 it was assumed that the bearing dynamic stiffness coefficient and damping coefficient were constant. However, the dynamic stiffness and damping of air bearings change with bearing clearance and rotational speeds.…”
Section: Introductionmentioning
confidence: 99%
“…They have revealed numerically the effect of the spindle imbalance and have shown that the eccentricity error motion of the spindle has a pronounced influence on the machining accuracy. Chen et al 20 performed dynamic analyses of an air spindle for ultra-precision fly cutting and investigated the effect of gas fluctuations on the aerostatic spindle on surface generation. In their study, it became clear that the rotational speeds of the spindle and the spindle imbalance directly affect the shape of the machined surface.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the bearing had better static and dynamic performance if there was an orifice located at the bottom of the bearing. Chen et al 11 discussed the effect of the unbalanced aerostatic spindle on the manufacturing surface. The conclusion indicated that rotation speed and unbalanced spindle directly affected manufacturing surface topography.…”
Section: Introductionmentioning
confidence: 99%